Symbole wykorzystywane w propagandzie wojennej okresu I wojny światowej w świetle ikonografii kart pocztowych = Symbols used in the warmongering during the First World War in the light of postcards iconography - Biszczanik, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
From the very beginning of the First World War, each command of armies fighting in the conflict believed that quick, effective postal service helps to maintain high morals at the battle-front and encourages both soldiers and their families to communicate. Among numerous papers devoted to postcards, only a few aimed at taking a deeper look at the development of the history of postcards during the First World War. During the military conflict in Europe, postcards were used as a mass medium of communication reaching the citizens of both metropolis and deep province. The publishers did not avoid any subject: postcards depict images of general staff meetings, the Emperor?s visit at the battle-front or soldiers in military casinos or latrines. Postcards from the First World War period depicted documentary photographies, reproductions of daily papers with spectacular news as well as images of places and events. One could also find there the portraits of war participants and victims, images of daily life in trenches at the battlefield, as well as nostalgic landscapes connected with the images of families. War, as time of international conflict, made it natural to depict various images of the enemy created in each country involved in the conflict.
Keywords: I (pierwsza) wojna światowa; ikonografia; pocztówka